2021
DOI: 10.1123/ijspp.2020-0579
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds Power Profiles and Performance in Youth Road Cycling

Abstract: Purpose: To analyze the anthropometric and physiological characteristics of competitive 15- to 16-year-old young male road cyclists and scale them according to a dichotomous category of successful/unsuccessful riders. Methods: A total of 103 15- to 16-year-old male road cyclists competing in the Italian national under 17 category performed a laboratory incremental exercise test during the in-season period. Age, height, body mass, body mass index, peak height velocity, and absolute and relative power output at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previous studies have investigated the relevance of absolute and relative power output (Gallo et al, 2021;Lee et al, 2002) and peak power (Faria et al, 2005) for success by relating performance data measured in a laboratory setting to success in outdoor competitions that are not directly related to that data. This study advances such work by focusing on mixed-reality sports platforms to analyze performance data from competition in combination with the directly corresponding competition outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have investigated the relevance of absolute and relative power output (Gallo et al, 2021;Lee et al, 2002) and peak power (Faria et al, 2005) for success by relating performance data measured in a laboratory setting to success in outdoor competitions that are not directly related to that data. This study advances such work by focusing on mixed-reality sports platforms to analyze performance data from competition in combination with the directly corresponding competition outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Race success correlates with the peak power an athlete is able to perform in a laboratory test (Faria et al, 2005). Thus, it can be noted that the outcome of a cycling race depends on power-to-weight characteristics (Gallo et al, 2021;Lee et al, 2002). Van Erp and Sanders, (2020) show that in professional cycling races maximum mean power over shorter durations (<5 min) are higher for riders who are placed in the top-10 of a race than for riders who are not in the top-10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, evidence suggests that superior race results from U17 onward are associated with a PRO road cycling career. In a recent study, Gallo et al 13 reported that U17 riders who scored at least one point in the annual Italian national ranking possess significantly higher absolute and relative power output at 2 and 4 mmol•L −1 of blood lactate concentration compared with riders who did not score points. Menaspà et al 9 found that higher classified cyclists in U19 annual Italian national ranking have higher physiological aerobic characteristics compared with cyclists who scored less points.…”
Section: Differences In Success Between Pro and Non-promentioning
confidence: 99%
“…Some previous studies already described external and internal training characteristics of PRO men and women [3][4][5] and U23 men [3,6] cyclists. However, to the best of our knowledge, no studies have reported training characteris tics of JUN cyclists yet [7]. In a recent study, the crosssectional dif ferences in external and internal race demands between JUN, U23 and PRO have been investigated [8].…”
Section: Introductionmentioning
confidence: 99%